IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2008 TENTANG RETRIBUSI TERMINAL DI KOTA SINGKAWANG - Melya Astriani E.42009089 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This research is intended to generate recommendations of implementation of terminal retribution policy in the Singkawang City. The title was selected based on the implementation of the terminal retribution problems that have not hit the target as specified and even at 2009-2011 period the realization of revenues has been decreased. This research uses descriptive study with a qualitative approach. The location of this research is in the terminals of Singkawang City and the subjects are the apparatus in the Department of Transportation, Communication and Information that related to implementation of the terminal retribution, and the driver who required to pay retribution. The conclusion of this study is the lack of understanding in each person who required to pay the retribution about the implementation of terminal retribution policy, inadequate facilities, lack of information about the guidelines of the policy implementation, disposition of the policy implementers who are not accompanied by a good responsibilities, inadequate incentives, and coordination among bureaucratic units are still not optimal. Keyword : implementation of public policy, communication, resources, disposition and bureaucracy structure.